Der Türken- und Türkeidiskurs in Schulbüchern 1919-1945 Zwischen Wissenszuwachs und Stagnation - Mathie, Dennis (Wie die Türken in unsere Köpfe kamen. Eine deutsche Bildungsgeschichte, 2023)
The much-vaunted interwar period after World War I and before World War II was also a phase of in-between for German-Turkish relations: It ranged from the founding of nation-state republics in Germany and Turkey together with their comprehensive social and political changes to the years of the Nazi regime and Atatürk's government. Against this background, this study examines the knowledge about Turkey that is conveyed in German textbooks for the subjects of history and geography and that is considered worthy of being handed down. In doing so, it becomes clear how much textbook knowledge participated in the reproduction of outdated stereotypes, but also in the narrative that deals with the ""long past"" of the ""bond between our two peoples"" (Theodor Heuss).